Distributed Computing : 29th International Symposium, DISC 2015, Tokyo, Japan, October 7-9, 2015, Proceedings - Moses, Yoram; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the proceedings of the 29th International Symposium on Distributed Computing, DISC 2015, held in Tokyo, Japan, in October 2015. The 42 full papers and 14 short papers presented in this volume were carefully reviewed and selected from 143 submissions. The papers feature original contributions to theory, design, implementation, modeling, analysis, or application of distributed systems and networks.
Keywords: Computer Communication Networks; Data structures (Computer scienc; Software engineering; Computer Communication Networks; Data Structures and Information Theory; Software Engineering; Information Systems Applications (incl. Internet).